Terpenoids and coumarins isolated from the fruits of Poncirus trifoliata - Xu, Guang-Hua; Kim, Jeong-Ah; Kim, So-Young; Ryu, Jae-Chun; Kim, Young-Soo; Jung, Sang-Hun; Kim, Mi-Kyeong; Lee, Seung-Ho (PHARMACEUTICAL SOC JAPAN, 2008)
Four new triterpenes, 21 alpha-methylmelianodiol (1), 21 beta-methylmelianodiol (2), hispidol A 25-methyl ether (3) and hispidol B 25-methyl ether (4), and a new coumarin, isoschininallylol (55), were isolated from the fruits of Poncirus trifoliata RAFINESQUE, along with seventeen known compounds. The structures of the new compounds (1-5) were elucidated by interpretation of their spectroscopic data.
Keywords: AGGREGATION CONSTITUENTS; ZANTHOXYLUM-SCHINIFOLIUM; CITRUS-HASSAKU; JUICE OIL; DERIVATIVES; TRITERPENOIDS; BIOSYNTHESIS; INHIBITION; RELEASE; CELLS